THE EFFECT OF THE PRODUCTION BUDGET ON THE SMOOTH PRODUCTION OF TAPIS MARGA KAYA’S MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) - Sri Surya Mandala; Kasmi Kasmi (STMIK Pringsewu, 2023)
Tapis Marga Kaya is one of the micro, small and medium enterprises (MSME) engaged in the manufacture of Tapis Cloth. The preparation of the production budget is basically planning how much the budgeted costs will be for the coming year. The preparation of the production budget has a broader scope, including with regard to how many products will be produced, how the production process will be carried out, and how much budget will be spent on the production process. The problem faced in this study is how the influence of the production budget on the smooth production of Tapis Marga Kaya. Data collection techniques in this study were carried out by conducting interviews, observing documentation, literature studies and questionnaires, using qualitative and quantitative analysis. The data was taken using a questionnaire which was distributed to 16 employee respondents at Tapis Marga Kaya. From the results of data processing, it was found that the price (r) = 0.6947 which has a fairly strong correlation and the value of t-count = 4.6512 when compared with the t-table at the 95% confidence level with a 5% degree of error obtained at 1.782. Because the value of t-count> t-table, then the hypothesis put forward can be accepted. The conclusion drawn is that the budget is reduced by 2.62%. There is an increase in the smooth production of 26.15%. This means that Tapis Marga Kaya can prepare the production budget. Suggestion, calculate carefully first before preparing the production budget.